Diseño e implementación de un ambiente virtual de aprendizaje para mejorar la competencia comunicativa lectora en los estudiantes del grado noveno del colegio de la Universidad Antonio Nariño, sede Usme - Prieto Prieto, Edgar Edison (Universidad Antonio Nariño, 2021)
The research aimed to improve reading communication skills through the design and implementation of a virtual learning environment (AVA) as a teaching tool for students in the ninth grade of the college of the Universidad Antonio Nariño, headquarters Usme. For this reason, the research had three specific objectives: the first was to identify the level of performance in which the students were using a pre-post test instrument, the second was the implementation of the design of an AVA, during three months where the Students carried out activities corresponding to the reading of continuous and discontinuous texts to strengthen the semantic, syntactic and pragmatic components. And finally, it was to know the results to offer recommendations to the students and to the educational institution where it was evidenced that at the minimum performance level it advanced 2%, satisfactory there was a decrease of 3% and advanced it increased 1%.